2009
DOI: 10.1097/tp.0b013e3181ba06ee
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Renal Function in Older Kidney Transplant Patients Following Delayed Versus Immediate Tacrolimus Administration

Abstract: Delayed tacrolimus with basiliximab induction did not provide an advantage in preserving renal function or reducing delayed graft function in older kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Total CNI avoidance, 3,5,9 -38 CNI minimization, 17,39 -55 and delayed introduction of CNI 49,50,[55][56][57][58][59][60][61][62] were investigated in 32 (n ϭ 5791), 17 (n ϭ 4131), and 10 studies (n ϭ 1519) respectively. Two studies 50,55 investigated CNI delay followed by minimization: to avoid "double counting" these were analyzed as "delay" studies initially, but if subgroup analyses were necessary (due to heterogeneity), then the same study was considered separately in both the "minimization" and "delay" subanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Total CNI avoidance, 3,5,9 -38 CNI minimization, 17,39 -55 and delayed introduction of CNI 49,50,[55][56][57][58][59][60][61][62] were investigated in 32 (n ϭ 5791), 17 (n ϭ 4131), and 10 studies (n ϭ 1519) respectively. Two studies 50,55 investigated CNI delay followed by minimization: to avoid "double counting" these were analyzed as "delay" studies initially, but if subgroup analyses were necessary (due to heterogeneity), then the same study was considered separately in both the "minimization" and "delay" subanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…They found that tacrolimus troughs were significantly lower day 5 and 7 post transplant in patients with ACR within the first 3 months than those that had no episodes of rejection ( P = 0.009, 0.006) . Delaying tacrolimus in the setting of basiliximab induction had no effect on ACR or DGF in a randomized controlled trial conducted by Andres and colleagues, however ( n = 132, each group) . Barraclough and colleagues demonstrated a significant increase in ACR within the first month post transplant in patients in the lowest tertile of drug exposure POD#4 (as measured by AUC) to combined cellcept, prednisone and tacrolimus vs. the remainder of patients in the middle and highest tertiles of exposure ( P = 0.001).…”
Section: Induction To Facilitate Calcineurin Inhibitor Minimizationmentioning
confidence: 98%
“…When addressing chronic immunosuppression, there is receding evidence to support delayed introduction, avoidance or withdrawal of calcineurin inhibitors (CNI). CNIs have recognized vasoconstrictive properties and their discontinuation in presence of DGF appears intuitive but may be nonbeneficial or even harmful (184,185). Recently, 254 patients, on average age 66 years old, were enrolled in a randomized open label trial to study early posttransplant tacrolimus dosing strategies (169).…”
Section: Treating Dgfmentioning
confidence: 99%